Photonics Breakthroughs 2024: Multidimensional Integrated (de)Multiplexers for Optical Fiber Communications - Xianyi Feng; Wu Zhou; Hao Chen; Yuzhe Ma; Yeyu Tong (IEEE Photonics Journal)
The growing demand for higher data transmission capacity, particularly driven by advancements in artificial intelligence and cloud computing, has spurred the exploration of various degrees of freedom (DoF) of light in optical communication systems, including wavelength, polarization, and spatial modes. Consequently, multidimensional optical multiplexing has emerged as a pivotal enabling technology. However, the development of compact, cost-effective, and scalable multidimensional optical interconnects remains a significant challenge. In this work, we present our recently demonstrated ultra-compact multiplexer fabricated on silicon, capable of selectively launching eight spatial and polarization modes into a few-mode optical fiber with a footprint of less than $35× 35$ μ $\mathrm{m^{2}}$ . The corresponding peak experimental coupling efficiencies for linearly polarized (LP) modes $\text{LP}_{01-x/y}$ , $\text{LP}_{11a-x/y}$ , $\text{LP}_{11b-x/y}$ , and $\text{LP}_{21b-x/y}$ are −3.8 dB, −5.5 dB, −3.6 dB, and −4.1 dB, respectively. Compared with previous approaches, our device facilitates the selective excitation of different LP modes in an ultra compact manner, while preserving polarization diversity and competitive coupling efficiencies. Additionally, we review recent advancements in multidimensional optical multiplexing based on photonic integrated circuits. We also address the principal challenges associated with our proposed methodologies and discuss future directions, including strategies for enhancement and potential applications.